Class 2 integrons dissemination among multidrug resistance (MDR) clones of Acinetobacter baumannii - Ramirez, Maria Soledad (2012)
Acinetobacter baumannii has emerged as a serious problem in the hospital environment at a global scale. Previous results from our laboratory showed a high frequency of class 2 integrons in A. baumannii strains from Argentina regarding the low rate of this element in A. baumannii isolates from the rest of the world. To reveal the current epidemiology of class 2 integrons, a molecular surveillance analyzing 78 multidrug resistant (MDR) A. baumannii isolates from Argentina and Uruguay was performed, exposing the presence of class 2 integron in the 36.61% of the isolates. Class 2 integron characterization showed that the typical Tn7::In2-7 array was present in 26 out of 27 intI2 positive isolates. All intI2 positive isolates contained at least one of the Tn7 transposition genes. In addition, we identified that 18 intI2 positive isolates possessed the Tn7::In2-7 within the attTn7 site. The molecular typing evidenced that clones I and IV that do not belong to widespread European clones I and II were found among the intI2 positive isolates. Our results exposed the widely dissemination of class 2 integron among MDR A. baumannii isolates from Argentina and Uruguay, also showing the persistence of two novel clones in our region, which could explain in part the high frequency of class 2 integron found in our region.